2019
DOI: 10.1108/ijaim-03-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Audit quality, media coverage, environmental, social, and governance disclosure and firm investment efficiency

Abstract: Purpose The purpose of this study is twofold: first, to introduce two determinants of environmental, social and governance (ESG) disclosure transparency, namely, audit quality and public media exposure; and second, to investigate the impact of ESG transparency on firm-level investment efficiency. Design/methodology/approach Ordinary least square (OLS) regressions are applied to explore the relationship between the two variables of interest (audit quality and public media exposure) and ESG transparency on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 110 publications
(183 reference statements)
4
93
0
3
Order By: Relevance
“…This commission is composed by non-executive directors, with no executive functions. Hammami and Hendijani Zadeh (2019) showed that the quality of the audit is an important factor in the transparency of the disclosure of social and governmental responsibility. On the other hand, Khlif and Souissi (2010) demonstrated that large auditing companies exert more pressure on their clients by improving their sustainable disclosure policies in terms of quantity, quality and timely disclosure to increase investor confidence in companies' annual and interim information.…”
Section: Influence Of Corporate Governancementioning
confidence: 99%
“…This commission is composed by non-executive directors, with no executive functions. Hammami and Hendijani Zadeh (2019) showed that the quality of the audit is an important factor in the transparency of the disclosure of social and governmental responsibility. On the other hand, Khlif and Souissi (2010) demonstrated that large auditing companies exert more pressure on their clients by improving their sustainable disclosure policies in terms of quantity, quality and timely disclosure to increase investor confidence in companies' annual and interim information.…”
Section: Influence Of Corporate Governancementioning
confidence: 99%
“…DeAngelo (1981) defines audit quality as the market-assessed likelihood of detecting and reporting deviations in the financial statements from the regulated standards. Prior studies (Francis and Wang, 2008;Lawrence et al, 2011;Hammami and Hendijani Zadeh, 2019;Shahzad et al, 2019) suggest that the Big 4 auditors critically assess the risk of managerial opportunism in order to identify material errors and misrepresentations in the accounting system. Signalling theory suggests that the presence of Big 4 auditors enhances the credibility and reputation of firms, which enables them to send positive signals to the market (Morris, 1987).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, it is necessary to conduct an audit not only at the final stage of project implementation, but also to determine the rationality of resource allocation by the state already at the planning stage. Therefore, the article proposes to determine the audit algorithm in terms of control of the following functions of public administration (Abdullah et al, 2018;Hammami and Hendijani Zadeh, 2019;Vasylishyn and Yarova, 2020).…”
Section: Achievability Of Strategic Objectivesmentioning
confidence: 99%